Doxorubicin Conjugated γ-Globulin Functionalised Gold Nanoparticles: A pH-Responsive Bioinspired Nanoconjugate Approach for Advanced Chemotherapeutics - Gaurav Chauhan; Vianni Chopra; América García Alvarado; Jocelyn Alexandra Gómez Siono; Marc J. Madou; Sergio Omar Martinez-Chapa; Manish M. Kulkarni (MDPI AG, 2024)
Developing successful nanomedicine hinges on regulating nanoparticle surface interactions within biological systems, particularly in intravenous nanotherapeutics. We harnessed the surface interactions of gold nanoparticles (AuNPs) with serum proteins, incorporating a γ-globulin (γG) hard surface corona and chemically conjugating Doxorubicin to create an innovative hybrid anticancer nanobioconjugate, Dox-γG-AuNPs. γG (with an isoelectric point of ~7.2) enhances cellular uptake and exhibits pH-sensitive behaviour, favouring targeted cancer cell drug delivery. In cell line studies, Dox-γG-AuNPs demonstrated a 10-fold higher cytotoxic potency compared to equivalent doxorubicin concentrations, with drug release favoured at pH 5.5 due to the γ-globulin corona's inherent pH sensitivity. This bioinspired approach presents a novel strategy for designing hybrid anticancer therapeutics. Our study also explored the intricacies of the p53-mediated ROS pathway's role in regulating cell fate, including apoptosis and necrosis, in response to these treatments. The pathway's delicate balance of ROS emerged as a critical determinant, warranting further investigation to elucidate its mechanisms and implications. Overall, leveraging the robust γ-globulin protein corona on AuNPs enhances biostability in harsh serum conditions, augments anticancer potential within pH-sensitive environments, and opens promising avenues for bioinspired drug delivery and the design of novel anticancer hybrids with precise targeting capabilities.